An analysis of research trends of inland waterway utilizing social network analysis - Young-Seo Choi; Gi-Tae Yeo (Asian Journal of Shipping and Logistics (AJSL), 2023)
This study aimed to analyze the research trends of inland waterways in the field of logistics by compiling previous studies that contain keywords related to inland waterways. To investigate the research trend, this study used a keyword network among the SNA methodology and deduced results using the concepts of centrality, including degree centrality, betweenness centrality, closeness centrality, and eigenvector centrality. According to the results of the comprehensive analysis by each region based on the eigenvector centrality outcome, Europe had a core keyword of modal shift, which refers to the conversion to eco-friendly vehicles due to the exhaust problem of land carriage, as well as the continuously implemented government policy. The results of China showed that the country's task to solve was on studies aimed at reducing traffic jams in inland waterways using AIS data. In the case of the US, the problems of ship delay remain unsolved owing to old locking facilities and equipment. This study provided academic implications that clarify the state-of-the-art in this research topic in three regions that have advanced inland waterways.
Keywords: 650; China; Europe; Inland waterway; Research Trend; Social Network Analysis (SNA); USA